Risk ratio assessment of key parameters affecting main engine starting system failures on container ships - Sarki, Furkan; Ekmekcioglu, Araks; Yigit, Kenan; Savas, Omer (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This paper analyzes failures associated with the main engine starting system, a component critical for ensuring operational continuity in maritime transport. The initial start-up process of the main engine plays a crucial role in both port maneuvers and navigational safety, and malfunctions during this process directly affect the safety and efficiency of ship operations. In this study, a Taguchi-based approach was applied to identify the factors affecting the occurrence of main engine starting system failures in container ships and to examine the effects of these factors on the frequency of failures. This approach allows for the statistically significant evaluation of interactions by optimizing the number of observations in multivariate systems. The results showed that the most important factor affecting the frequency of main engine starting system failures was the age of the ship (43.9 %), followed by the failure type of main engine starting system (21.0 %) and the ship's carrying capacity (2.4 %), respectively. The findings indicate that mechanical wear and system fatigue increase with the age of the ship; therefore, maintenance planning should be optimized according to the age factor.
Keywords: Main engine; Failure analysis; Risk assessment; Taguchi method; RELIABILITY; MARINE; Engineering; Oceanography